Investigasi Faktor Niat Pembelian terhadap Merek Kosmetik Mewah di Indonesia - Andina Fasha; Winnie Kho; Arienda Gitty Ramadani; Erilia Kesumahati (Penerbit Goodwood, 2025)
Purpose: The objective of this investigation is to identify the variables that affect purchase intention, including product quality, service quality, e-WOM, and brand image. Methodology/approach: The method used is quantitative. The result source is the Google Form questionnaire. Results/findings: This study's findings reveal that product quality, EWOM, and brand image are proven to have a significant influence on purchase intention. However, the service quality variable has not been proven to influence purchase intention significantly. Conclusions: The results indicate that consumers’ purchase intention toward luxury cosmetic brands is primarily shaped by tangible product performance, strong brand reputation, and credible online word-of-mouth communication. Service quality, while still relevant for customer retention, does not play a critical role at the intention stage. Thus, luxury cosmetic managers should focus more on strengthening product excellence, managing e-WOM credibility, and reinforcing consistent brand image across digital channels. Limitations: The results are based on a single-city cross-sectional survey of Batam consumers and rely on self-reported evidence quantitative, which may limit generalizability and introduce common method bias. Future studies should use longitudinal or multicity designs, incorporate objective behavioural measures, and test moderator variables (e.g., customer satisfaction or brand loyalty) to deepen causal insights. Contribution: The findings suggest that luxury cosmetic brand managers should prioritize superior product quality, active management of electronic word-of-mouth promotion, and consistent brand image building to enhance purchase intention; service quality, while necessary for loyalty, appears to be less determinant at the intention stage.